Outcomes of different types of intermittent fasting for practitioners in terms of nutritional status and quality of life: A systematic review - Nur Asma Mohd Hafizi, Nurul Syazwani Azhari, Asma’ Ali, Noor Salihah Zakaria, Hayati Mohd Yusof (Journal of Applied Pharmaceutical Science, 2023)
Intermittent fasting (IF) is a method of restricting energy intake or shortening the period of feeding of an individual. It is one of the dietary strategies that have been developed to treat overweight and obesity and has become popular and widely adopted. IF diets have several different types. Thus, this study aims to review the outcomes of different types of IF for practitioners in terms of their nutritional status and quality of life (QoL). Electronic databases (ScienceDirect and Wiley Online Library) were used to search for relevant articles. The keywords used were “IF” OR “intermittent energy restriction” OR “time-restricted feeding” OR “alternate day fasting” OR “5:2 diet” AND (“energy intake” OR “caloric consumption”) AND (“nutritional status” OR “health condition”) AND (“QoL” OR “changes in lifestyle”). Nutritional status outcomes highlighted that most people following IF diets were able to reduce weight, fat mass, and waist circumferences. IF also improved the lipid profile, fasting blood glucose, insulin, and blood pressure. As for the QoL, some studies highlighted improvements in emotional well-being after the trials; however, inconsistent results were obtained in terms of the physical activity domain. Different geographical areas covered in the articles reviewed might contribute to inconsistent findings related to the physical activity domain and thus become a limitation in this review. In conclusion, IF intervention, regardless of type, was able to show improvement in anthropometry and QoL.
Keywords: 5:2 diet, alternate day fasting, intermittent energy restriction, nutritional status, quality of life, time-restrict